2022
DOI: 10.26599/ntm.2022.9130010
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the organic semiconducting photosensitizers for hypoxia-tolerant type I photodynamic therapy

Abstract: Photodynamic therapy (PDT) is a promising approach to treat cancer and microbial infections due to its minimal invasiveness, high spatiotemporal selectivity, tissue specificity, and low toxicity. Depending on the reactive oxygen species generation mechanisms, PDT can be classified as type I and type II. To date, most reported photosensitizers are based on the type II PDT mechanism, which produces toxic singlet oxygen and requires an abundant and continuous supply of oxygen molecules. Unfortunately, in typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Organic semiconductors are active materials in high-end displays, 1,2 solar cells, 3,4 biosensors, 5 lasers, 6,7 and photosensitizers for therapy. 8 From biology to lighting technologies, the molecular excited-state behavior is determined by the interplay between photonic, electronic, spin, and nuclear degrees of freedom. Understanding excited-state behavior is key for technology development, in particular, developing strategies to utilize excited states that conventionally exhibit unfavorable characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic semiconductors are active materials in high-end displays, 1,2 solar cells, 3,4 biosensors, 5 lasers, 6,7 and photosensitizers for therapy. 8 From biology to lighting technologies, the molecular excited-state behavior is determined by the interplay between photonic, electronic, spin, and nuclear degrees of freedom. Understanding excited-state behavior is key for technology development, in particular, developing strategies to utilize excited states that conventionally exhibit unfavorable characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Organic semiconductors are active materials in high-end displays, , solar cells, , biosensors, lasers, , and photosensitizers for therapy . From biology to lighting technologies, the molecular excited-state behavior is determined by the interplay between photonic, electronic, spin, and nuclear degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–9 ] Type I and Type II PDT generally occur together, and the extent of the reactions depends on the PSs type, substrate species, and O 2 concentration. [ 6,10 ] Noteworthily, certain existing studies have indicated that Type II PDT is usually dominant in the photodynamic process, since it requires lower excitation energy to produce 1 O 2 . [ 11,12 ] Currently, most types of PSs used in clinical practices are based on Type II PDT processes.…”
Section: Introductionmentioning
confidence: 99%